2021
DOI: 10.1088/1361-6501/ac3678
|View full text |Cite
|
Sign up to set email alerts
|

Photon force microelectromechanical system cantilever combined with a fibre optic system as a measurement technique for optomechanical studies

Abstract: In this paper we present a metrological measurement technique that is a combination of fibre optic interferometry and a microelectromechanical system (MEMS) sensor for photon force (PF) measurement with traceability via an electromagnetic way. The main advantage of the presented method is the reference to the current balance, which is the primary mass/force metrological standard. The MEMS cantilever is a transducer of the photon force to the deflection that can be compensated with the use of the Lorentz force.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In the same work 24 , the authors showed that the detection of photon force is possible with this type of the device. The performed experiment covered the harmonic actuation of the microcantilever with modulated laser light.…”
Section: Methodsmentioning
confidence: 94%
“…In the same work 24 , the authors showed that the detection of photon force is possible with this type of the device. The performed experiment covered the harmonic actuation of the microcantilever with modulated laser light.…”
Section: Methodsmentioning
confidence: 94%